Obrona ważności małżeństwa w perspektywie poszukiwania prawdy o małżeństwie w czynnościach obrońcy węzła małżeńskiego - Bartczak, Adam (Ius Matrimoniale, 2009)
The article analyses role of the defender marital knot in the cases of declaration of the nullity of a marriage. The basic question is: what is the place in the process, what is the rights and obligations of the defender marital knot? Is he defends the validity of marriage at all costs? Benedict XIV’s Constitution Dei miseratione and the Code of Canon Law from the year 1917 give that basic obligation of the defender is defense of marriage. Later this concept evolved. In the Code of Canon Law from the year 1983 we have following meaning. The defender defends the validity of marriage, but not at all costs. This defense must be rational. We have also this statement in the process’s instruction Dignitas connubii. In conclusion, Author stats that efender defends the validity of marriage with regard to the truth.